Language Shift Among Saudi Children Studying in Riyadh International Schools: Fact or Fiction? - Alyami, Nasiba Abdulrahman (International Journal of Language and Literary Studies, 2024)
The study aimed at identifying whether there exists a language shift towards English among Saudi children studying in international schools in Riyadh. This was approached through investigating the code choices they prefer to use in different life domains (such as the home domain (parents and siblings), school domain (friends and teachers), neighbors, and relatives…etc.), i.e. from their parents' perspectives. To achieve the aim of the study, a descriptive survey approach was followed, where the study sample consisted of (382) parents. The questionnaire was also used as a data collection tool. The results revealed that Saudi children studying in international schools in Riyadh showed different tendencies towards language choice, while communicating in different domains. More specifically, they tend to use English more than their native tongue (Arabic) in daily spontaneous communication. The findings thus indicate that the children are in fact going through early stages of Language Shift.